IDENTIFICATION AND ANALYSIS OF ECONOMIC FACTORS AFFECTING RURAL UNDERDEVELOPMENT IN AFGHANISTAN - Mazloum Yar, Fayaz Gul; Yasouri, Majid; Widya Astuti, Aurelia (Riviera Publishing, 2022)
Developing countries often face the challenge of underdeveloped rural areas, resulting in adverse impacts such as poverty, unemployment and migration. Therefore, it is very important to prioritize rural development and improve the living conditions of rural residents. This research aims to identify and analyze economic factors that contribute to village underdevelopment in Afghanistan. This research uses a combination of field studies, Expert Choice software, interviews with experts, and credible library sources for data collection. The statistical population consists of experts, university professors, and individuals involved in rural economic development. We collected data through face-to-face interviews and questionnaires. We used confirmatory factor analysis and coefficient of variation for data analysis. These findings reveal that there are several factors that contribute to rural underdevelopment in Afghanistan. These factors include management problems, especially the prevalence of unskilled labor in rural economic activities. Financial problems, such as inadequate credit and investment in rural areas, also play a role. Limited social participation and low involvement of women in rural activities are other contributing factors. Environmental problems, such as inappropriate use of underground water resources, further exacerbate this problem. In addition, physical challenges, such as weak or non-existent rural-urban communication networks and other related problems, also contribute to rural underdevelopment. Addressing and overcoming these fundamental barriers and challenges is critical to achieving rural development and overall national development. Furthermore, this research identifies key factors of rural development in the economic sector.